Easy‐to‐use algorithm would provide faster diagnoses for mucopolysaccharidosis type I and enable patients to receive earlier treatment - Tylki‐Szymańska, Anna; De Meirleir, Linda; Di Rocco, Maja; Fathalla, Waseem M.; Guffon, Nathalie; Lampe, Christina; Lund, Allan M.; Parini, Rossella; Wijburg, Frits A.; Zeman, Jiri; Scarpa, Maurizio (Acta Paediatrica, 2018)
Aim The aim of this study was to develop an algorithm to prompt early clinical suspicion of mucopolysaccharidosis type I (MPS I). Methods An international working group was established in 2016 that comprised 11 experts in paediatrics, rare diseases and inherited metabolic diseases. They reviewed real‐world clinical cases, selected key signs or symptoms based on their prevalence and specificity and reached consensus about the algorithm. The algorithm was retrospectively tested. Results An algorithm was developed. In patients under two years of age, kyphosis or gibbus deformity were the key symptoms that raised clinical suspicion of MPS I and in those over two years they were kyphosis or gibbus deformity, or joint stiffness or contractures without inflammation. The algorithm was tested on 35 cases, comprising 16 Hurler, 10 Hurler–Scheie, and nine Scheie patients. Of these 35 cases, 32 (91%) – 16 Hurler, nine Hurler–Scheie and seven Scheie patients – would have been referred earlier if the algorithm had been used. Conclusion The expert panel developed and tested an algorithm that helps raise clinical suspicion of MPS I and would lead to a more prompt final diagnosis and allow earlier treatment.